Upaya Pembuktian Surat Dakwaan Berbentuk Alternatif oleh Penuntut Umum dalam Tindak Pidana Pengrusakan - Alfian Anhan Orlando (Sebelas Maret University, 2019)
This study aims to determine the role of the public prosecutor in an attempt to prove his indictment on a criminal case of vandalism related to whether it is in accordance with Article 184 paragraph 1 of the Criminal Procedure Code. The type of research used is normative and prescriptive legal research. The research approach used is qualitative. Sources of legal material of this research in the form of primary legal materials and secondary legal materials. The collection of legal materials used is a technique with literature study or document studies, while the analytical technique used is a syllogistic technique that uses deductive thinking patterns. The evidentiary efforts made by the public prosecutor are correct and are in accordance with article 184 peragraph 1 KUHAP which in the article regulates the valid evidence of witnesses, expert statements, letters, instructions, and statements of the accused. In the case of this trial the prosecutor has succeeded in presenting at least 2 evidences. The evidence presented is the witnesses and statements of the defendant who are accompanied by evidence successfully fled in the hearing. The prosecutor succeeded in proving that all the evidences presented had mutually conformed to each other and also provided information in accordance with the accused article.Keywords: Evidence, Criminal Act of Destruction